If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10g + -1g = 9 Combine like terms: 10g + -1g = 9g 9g = 9 Solving 9g = 9 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by '9'. g = 1 Simplifying g = 1
| 8=20-2n | | 4(9+3x)-12=6 | | 4x+1x+4=8x-3x+4 | | X+6+7-5=18+4 | | -14=h+7 | | 5(t-87)=10 | | -5(c-89)=-30 | | 13.7b-3=3.43b | | 74-2x=89-3x | | 13.7b-3=3-43b | | 48=12xn | | 19=5a-6 | | -189=-2x-3(7x+17) | | 81-x=94-2x | | 99.60=9.1a+72.3 | | 36=9(r-2) | | 70-3x=130-43x | | 35+42=12+x | | 9x+9=8x+4 | | 5x+7(7+3x)=4(9-8)+7 | | X+19=7+20 | | 99=98s+1 | | 8a^2+10ab^2+4ab+5b^3=0 | | 81-2x=92-3x | | 28=2w+24 | | f(0)=2x^3-5 | | 1.5sin(x)=sin(3x) | | 5x-17=12x-4 | | 2y^2+8y+2=0 | | 2(x+7)-6=x+15 | | (2x^3y^2)= | | (1-4y)(5-y)= |